A Guide to municipal investments in the Philippines. - Local Government Development Foundation (Manila Local Government Development Foundation, 1994)
"This guide is an initial attempt to provide potential foreign and local investors with the necessary information which may lead to making a decision to invest in Philippine localities. The guide provides the user with a perspective of the basic socio-economic and other pertinent information about specific sectors and localities in the country. The guide contains information valuable not only to investors, but to local governments in generating economic activities is to create an awareness among investors of the necessary information for them to make sound business decisions." Part I introduces the user to the Philippine local government system- structure, powers and services. Part II shows the reader some financial information on industries and the employment status of labor in the country. Part III provides information on industries and the employment status of labor in the country. Part IV is an indicative illustration of the major agricultural, marine, mineral and other natural resources in the country. Part V shows the availability of power and energy, Part VI transportation infrastructure- roads, airports, seaports; part VII is on telecommunications - telephones, mobile phones, television, radio, postal services. The guide includes directories of shipping lines, airlines, and cargo forwarders operating in the country. For foreign investors, the addresses of Philippine embassies abroad and foreign embassies and consulates in Manila are also listed. Part VIII is a section on educational facilities that shows higher education institutions found in the country. Selected tourist spots have also been included for tourism promotion.
Keywords: Investments -- Philippines -- uidebooks; Municipal government -- Philippines -- Guidebooks; Cities and towns -- Philippines -- Guidebooks